Do demographics and tumour-related factors affect nodal yield at neck dissection? A retrospective cohort study. (27th October 2016) - Lim, R S; Evans, L; George, A P; de Alwis, N; Stimpson, P; Merriel, S; Giddings, C E B; Billah, B; Smith, J A; Safdar, A; Sigston, E
Abstract: Background: Nodal metastasis is an important prognostic factor in head and neck squamous cell carcinoma. This study aimed to determine the average nodal basin yield per level of neck dissection, and to investigate if age, gender, body mass index, tumour size, depth of tumour invasion and p16 status influence nodal yield. Method: A retrospective review of 185 patients with head and neck squamous cell carcinoma generated 240 neck dissection specimens. Results: The respective mean nodal yields for levels I, II, III, IV and V were 5.27, 9.43, 8.49, 7.43 and 9.02 in non-cutaneous squamous cell carcinoma patients, and 4.2, 7.57, 9.65, 4.33 and 12.29 in cutaneous squamous cell carcinoma patients. Multiple regression analysis revealed that p16-positive patients with mucosal squamous cell carcinoma yielded, on average, 2.4 more nodes than their p16-negative peers ( p = 0.04, 95 per cent confidence interval = 0.116 to 4.693). This figure was 3.84 ( p = 0.008, 95 per cent confidence interval = 1.070 to 6.605) for p16-positive patients with oral cavity squamous cell carcinoma. Conclusion: In mucosal squamous cell carcinoma, p16-positive status significantly influenced nodal yield, with the impact being more pronounced in oral cavity squamous cell carcinoma patients.